High-SMSR wavelength-swept laser with a CL-band mode-hopping free tuning range - Qiao, Shan; Sheng, Liwen; Huang, Lin; Zhang, Aiguo; Wei, Yu; Liu, Zhiming; Ju, Junwei; Zhang, Zhihui; Yin, Bingqi; Li, Peng; Han, Jilei; Zhang, Yiqi; et al. (Frontiers in Physics, 2023)
A high side-mode suppression ratio external-cavity wavelength-swept laser system with a wide mode-hopping free tuning range is developed. The proposed wavelength-swept laser is based on a single-angled facet gain chip in a classical Littman-Metcalf external-cavity configuration using a blazed diffraction grating as the feedback element. The output power, side-mode suppression ratio, and tunable range of the external-cavity wavelength-swept laser system are experimentally measured. A wide mode-hopping-free continuous wavelength tuning range about 100 nm in CL-band with a side-mode suppression ratio of more than 65.64 dB is realized. An output optical power of more than 14.12 dBm over the entire tunable region can also be achieved. The proposed external-cavity wavelength-swept laser system allows simultaneously high side-mode suppression ratio and no mode-hopping tunable radiation, thus opening a door for practical applications such as optical modulation schemes.